"THE IMPORTANCE OF DRAMA METHOD IN LEARNING ESL" - Mirusmonova Ziyoda Ziyodullo qizi; Ergasheva Muqaddas Toshtemirovna (Modern American Journals, 2025)
This article examines the effectiveness of drama in learning English as a second language (ESL). Drama-based activities such as role-playing, improvisation, and storytelling enable students to develop speaking, listening, and critical thinking skills in a fun and interactive environment. Drama helps create a safe space where students can express themselves, gain confidence, and use language in real life. Research shows that drama significantly improves communication skills and increases fluency, especially among beginner and intermediate learners.